Supramolecular assembled nanogel made of mannan - Ferreira, Sílvia A. (2010)
Introduction: The supramolecular assembled nanogel made of mannan was synthesed and characterized with the purpose to obtain a potential pharmaceutical delivery system able to work both as a therapeutic and prophylactic vaccine adjuvant and antigen carrier. These systems are expected to perform as carriers for proteins and peptides, acting like antigens, optimizing delivery to antigen-presenting cells, by targeting their mannose receptors. Immunity might be improved conjugating this system with other immune response modifiers.